은 나노 와이어를 이용한 마이크로 슈퍼커패시터의 구조 개선 및 특성 분석 - 김명건 (The Graduate School, Ajou University, 2024)
마이크로 슈퍼커패시터는 전기 이중층 커패시터를 2 차원 평면으로 구조화하여 전하를 저장하는 소형 장치이다. 마이크로 슈퍼커패시터는 배터리에 비해 높은 출력 밀도와 긴 수명 특성을 가지며, 특히 소형화와 집적화가 용이하여 웨어러블 기기, 바이오센서, 마이크로 일렉트로닉스 등 다양한 소형 전자 기기의 에너지 시스템으로 주목받고 있다. 하지만 마이크로 슈퍼커패시터는 에너지 밀도, 유연성, 그리고 생산성 측면에서 해결해야 할 과제들이 있다. 본 연구는 은 나노 와이어와 활성탄을 이용한 집전체가 없는 새로운 형태의 전극을 소프트 리소그래피 공정으로 제작하는 방안을 제시한다. 은 나노 와이어는 우수한 전기 전도성과 유연성을 제공하며, 활성탄은 높은 비표면적과 다공성 구조로 인해 전기화학적 성능을 극대화할 수 있다. 두 재료의 혼합물을 이용하여 집전체와 활물질을 동시에 제작함으로써 공정을 간소화하여 시간과 비용을 절감할 수 있다. 이러한 방안으로 마이크로 슈퍼커패시터의 에너지 밀도를 높이고 유연성과 생산성을 개선하고자 한다. 샌드위치 구조와 인터디지털 구조의 마이크로 슈퍼커패시터를 제작하고, 각각의 혼합물 비율과 주사 속도에 따른 전기화학적 성능을 평가했다. 주요 시험 방법으로는 배터리 충∙방전 테스트기를 통해 정전류 충·방전 시험, 순환 전류-전압 주사법 등을 사용하였으며, 이를 통해 셀의 전기화학적 성능과 보존성을 평가하였다. 실험 결과, 샌드위치 구조와 인터디지털 구조의 마이크로 슈퍼커패시터는 각각의 혼합물 비율과 주사 속도에 따라 다른 전기화학적 성능을 보였다. 특히, 혼합물 비율이 샌드위치 구조의 경우 1:24, 인터디지털 구조의 경우 1:12 에서 가장 높은 단위 면적당 전기용량 (7.01 mF/cm2 ), 에너지 밀도 (10.60μWh/cm²)와 전력 밀도(0.49mW/cm²)를 나타냈으며, 안정성 시험에서도 우수한 유연성과 보존성을 보였다. 은 나노 와이어와 활성탄 전극을 활용하여 고해상도 마이크로 슈퍼커패시터의 새로운 형태의 전극과 간소화된 제작 공정을 제시함으로써 향후 소형 전자기기와 웨어러블 기기의 에너지 저장 장치로서의 활용 가능성을 제시한다.|Micro-supercapacitors are miniaturized devices that store charge by structuring electric double-layer capacitors in a two-dimensional plane. Compared to batteries, micro-supercapacitors have high power density and long lifespan characteristics, and are particularly noted for their _x000D_ ease of miniaturization and integration, making them attractive energy systems for various miniaturized electronic devices such as wearable devices, biosensors, and microelectronics. However, micro-supercapacitors face challenges in terms of energy density, flexibility, and productivity. This study proposes a method for fabricating a new type of current collector-free electrode using silver nanowires and activated carbon through a soft lithography process. Silver nanowires provide excellent electrical conductivity and flexibility, while activated carbon can _x000D_ maximize electrochemical performance due to its high specific surface area and porous structure. By using a mixture of these two materials to simultaneously fabricate both the current collector and the active material, the process can be simplified, leading to time and cost savings. _x000D_ This approach aims to enhance the energy density, flexibility, and productivity of micro-supercapacitors. Micro-supercapacitors with sandwich and interdigitated structures were fabricated, and their electrochemical performance was evaluated according to various mixture ratios and scan rates. The main experimental methods included constant current charge-discharge _x000D_ tests and cyclic voltammetry using potentiostat, through which the electrochemical performance and retention of the cells were evaluated. The experimental results showed that the micro-supercapacitors with sandwich and interdigitated structures exhibited different electrochemical performance depending on the mixture ratio and scan rate. Particularly, the mixture ratio of 1:24 for the sandwich structure and 1:12 for the interdigitated structure showed the highest areal capacitance (7.01 mF/cm²), energy density (10.60 μWh/cm²), and power density (0.49 mW/cm²), and also demonstrated excellent flexibility and retention in stability tests. By presenting a new type of electrode and simplified fabrication process for high-resolution micro-supercapacitors using silver nanowires and activated carbon electrodes, this study suggests the _x000D_ potential for future use as energy storage devices for miniaturized electronic devices and wearable technology.
학위논문(석사)--에너지시스템학과,2024. 8
Keywords: 마이크로 슈퍼커패시터; 은 나노 와이어